Growth restriction in pregnancies of opioid-dependent mothers. Issue 4 (13th April 2010) - Liu, A J W; Sithamparanathan, S; Jones, M P; Cook, C-M; Nanan, R
Abstract : Background and aims: Intrauterine growth restriction (IUGR) can lead to significant intellectual and behavioural problems in later life. IUGR represents a frequent feature of pregnancies of opioid-dependent mothers (ODMs), the causes of which are largely unknown. The objective of this study was to determine the independent risk factors for IUGR in ODMs. Design and subjects: We performed a retrospective study analysing maternal and neonatal parameters from pregnancies of ODM maintained on methadone (n=215). These were compared to smoking non-ODM and non-smoking non-ODM control groups matched for maternal age, gestational age at delivery, infant birth date and sex. Logistic regression analysis was performed on all parameters with the outcome of IUGR. Results: Fifty-seven infants (27%) of ODMs showed IUGR. Compared to non-smoking non-ODMs, the risk of IUGR in non-smoking ODMs was almost four times higher (relative risk 3.48, 95% CI 1.70 to 7.14). Growth restriction was independent of the last maternal methadone dose and the cumulative methadone dose during pregnancy. In addition, whereas nicotine and female sex impacted on IUGR in non-ODMs (nicotine: OR 3.45, 95% CI 1.82 to 6.67; sex: OR 2.37, 95% CI 1.25 to 4.50), these parameters had no influence on IUGR in ODMs. Maternal body mass index (BMI) was identified as the only independent risk factor for IUGR in infants of ODMs (OR 1.15, 95% CI 1.03 to 1.28). Conclusions: IUGR in pregnancies of ODM is related to maternal BMI rather than to opiate dosing, nicotine use or infant sex. BMI may itself be an indirect marker of several other genetic, nutritional and/or social determinants of IUGR.